2011
DOI: 10.1245/s10434-011-2153-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Preoperative Metabolic Tumor Volume and Total Lesion Glycolysis in Patients with Epithelial Ovarian Cancer

Abstract: Pretreatment metabolic parameters such as MTV and TLG showed statistically significant association with recurrence in patients with EOC. These values can be useful quantitative criteria for disease prognostication in patients with EOC before treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 27 publications
4
89
1
5
Order By: Relevance
“…In accordance with our results, we found that the inclusion of PET/CT in the management of patients with recurrent ovary cancer had an impact on the decision making in 42% of subjects. As reported in the literature, the change in management of patients with OC who have undergone FDG PET/ CT ranges between 25% and 58% (10,(15)(16)(17)(18). OC can disseminate to the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, we found that the inclusion of PET/CT in the management of patients with recurrent ovary cancer had an impact on the decision making in 42% of subjects. As reported in the literature, the change in management of patients with OC who have undergone FDG PET/ CT ranges between 25% and 58% (10,(15)(16)(17)(18). OC can disseminate to the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that GLUT-1 expression might be an independent prognostic factor in colon cancer [12]. As for malignant ovarian tumors, potential roles of GLUT-1 expression in predicting prognosis remain unclear, but an article recently published by Chung et al provides a clue to this matter [18]. They reported that the preoperative metabolic tumor burden and its distribution measured by SUV values could predict recurrence in patients with epithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1a-c). TLG was calculated by multiplying the mean SUV (SUVmean) of the primary tumor by metabolic volume of the tumor [8]. The SUVmax, MTV and TLG of primary lung lesions were recorded as SUVmax-lung, MTV-lung, and TLG-lung, respectively.…”
Section: Assessment Of Mtv Tlg and Suvmax Of Primary Lung Lesionmentioning
confidence: 99%
“…Standardized uptake value (SUV)-based PET parameter can predict therapeutic outcome and overall survival in many types of malignancies [6][7][8][9][10][11][12]. Recently, metabolic tumor volume (MTV) and total lesion glycolysis (TLG) have been reported as additional diagnostic and prognostic imaging biomarkers for maximum SUV (SUVmax) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%